Long-term clinical outcomes in patients with CIS treated with interferon beta-1b: results from the 15-year follow up of the BENEFIT trial - Kappos, Ludwig; Edan, Gilles; Freedman, Mark S; Hartung, Hans-Peter; Montalbán, Xavier; Barkhof, Frederik; Koelbach, Ralf; MacManus, David G; Wicklein, Eva-Maria (Journal of neurology, 2024)
Multiple sclerosis (MS) treatment intervention with immunomodulating therapy at early disease stage improves short term clinical outcomes. The objective of this study is to describe the long-term outcomes and healthcare utilization of patients with clinically isolated syndrome (CIS) included in the Betaferon®/Betaseron® in Newly Emerging MS for Initial Treatment (BENEFIT) randomized, parallel group trial. In BENEFIT patients were assigned to "early" IFNB-1b treatment or placebo ("delayed" treatment). After 2 years or conversion to clinically definite multiple sclerosis (CDMS), all patients were offered IFNB-1b and were reassessed 15 years later. Of 468 patients, 261 (55.8%) were enrolled into BENEFIT 15 (161 [55.1%] from the early, 100 [56.8%] from the delayed treatment arm). In the full BENEFIT analysis set, risk of conversion to CDMS remained lower in the early treatment group ( - 30.5%; hazard ratio 0.695 [95% CI, 0.547-0.883]; p = 0.0029) with a 15.7% lower risk of relapse than in the delayed treatment group (p = 0.1008). Overall, 25 patients (9.6%; 9.9% early, 9.0% delayed) converted to secondary progressive multiple sclerosis. Disability remained low and stable with no significant difference between groups in Expanded Disability Status Scale score or MRI metrics. Paced Auditory Serial Addition Task-3 scores were better in the early treatment group (p = 0.0036 for treatment effect over 15 years). 66.3% of patients were still employed at Year 15 versus 74.7% at baseline. In conclusion, results 15 years from initial randomization support long-term benefits of early treatment with IFNB-1b.
Keywords: výsledek terapie; Young Adult; Male; progrese nemoci; mladý dospělý; Multiple Sclerosis; následné studie; Demyelinating Diseases; Adult; dospělí; mužské pohlaví; Disease Progression; Follow-Up Studies; dvojitá slepá metoda; Treatment Outcome; lidé; ženské pohlaví; Humans; interferon beta 1b; Double-Blind Method; Female; lidé středního věku; demyelinizační nemoci; roztroušená skleróza; Interferon beta-1b; Middle Aged